Menjadi Sahabat bagi Sesama: Memaknai Relasi Persahabatan dalam Pelayanan Pastoral - Besly Yermy Tungaoly Messakh (Gema Teologika, 2020)
The capability to build relationships is important in doing pastoral ministry successfully. However, this factor is often neglected by a pastoral counsellor or pastoral caregiver. Many pastoral counsellors tend to improve their technical skills rather than capability to build a good relationship with the client. As a consequence, many persons in trouble feel unaccepted by their pastoral counsellor, leading to the situation of helplessness. Using the method of Christopraxis, this article attempts to respond to such situation. Christopraxis places the attitude and works of Jesus, as witnessed in the Gospel, as the fundamental reference and resource for today’s ministerial works. In this case, Jesus’ praxis of friendship is employed as the model of relationships in pastoral ministry. It is suggested that a pastoral ministry inspired by the radical and open friendship model that Jesus practised would off er a better approach than the feudalistic and paternalistic ones, commonly practised in Indonesia.